2010
DOI: 10.1016/j.agwat.2010.03.011
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of trunk diameter variation derived indices as water stress indicators in mature olive trees

Abstract: El artículo seleccionado no se encuentra disponible por ahora a texto completo por no haber sido facilitado todavía por el investigador a cargo del archivo del mismo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0
5

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 46 publications
1
23
0
5
Order By: Relevance
“…Some species such as grapevine may show isohydric or anisohydric behaviour, depending on the water stress conditions [29,36]. For other species, such as olive, a near-isohydric behaviour has been described, since they are able to keep relatively stable leaf water potentials but not as effectively as isohydric plants [37]. In the case of plants with isohydric behaviour, a significant decrease of g s occurs during the day while leaf water potential remains constant.…”
Section: Daily Growth Dg µMmentioning
confidence: 99%
“…Some species such as grapevine may show isohydric or anisohydric behaviour, depending on the water stress conditions [29,36]. For other species, such as olive, a near-isohydric behaviour has been described, since they are able to keep relatively stable leaf water potentials but not as effectively as isohydric plants [37]. In the case of plants with isohydric behaviour, a significant decrease of g s occurs during the day while leaf water potential remains constant.…”
Section: Daily Growth Dg µMmentioning
confidence: 99%
“…Rallo and Suarez (1989) observed that leaf length, number, and area as well as the dry weight of fruit-bearing branches increased rapidly in the spring with a plateau being reached approximately 60-100 days after bloom and little or no growth the rest of the season. Trunk growth may also slow sharply at about the same time (Cuevas et al, 2010), probably due to competition for assimilates with the fruit, which may be strong sinks after pit hardening (50-60 d after bloom). In contrast, Connor and Fereres (2005) have suggested that shoot elongation and leaf expansion may be maintained from spring to autumn if sufficient irrigation is provided.…”
Section: Introductionmentioning
confidence: 97%
“…There is a substantial amount of literature on the usefulness of different methods for the continuous monitoring of crop water status, such as those based on the use of dendrometers (Moriana et al, 2010or Cuevas et al, 2010, sap-flow (Fernández et al, 2008a;Fernández, 2014a) or leaf turgor pressure probes (Zimmerman et al, 2008;Fernández et al, 2011a). Studies on their applicability to commercial orchards proved that additional information on crop-water status is often required to properly evaluate the information collected by those sensors (Fernández, 2014b).…”
Section: Introductionmentioning
confidence: 99%